Public mental health stigma and suicide rates across Europe - Lara Oblak (Frontiers in Public Health)
IntroductionMental health stigma remains a significant public health concern, particularly due to its complex relationship with suicide risk. While the two phenomena appear to be closely connected, inconsistencies in stigma measurement and a lack of standardized instruments complicate efforts to fully understand its role in suicide occurrence and prevention.MethodsWe analyzed stigma measures from the 2022 and 2023 Eurobarometer surveys, alongside suicide rates and socio-economic indicators for 27 European Union countries. Correlational analyses and hierarchical linear regression models were employed to assess the relationships between stigma-associated variables and national suicide rates.ResultsOur analysis revealed a notable decline in suicide rates between 2010 and 2019, with only four countries reporting increases. We found multiple negative associations between suicide rates and stigma measures, notably for the belief that disclosing a mental health condition would negatively impact one's career. Hierarchical linear regression models supported this item as a significant predictor of lower suicide rates.DiscussionThe findings underscore the need for more systematic, theory-driven approaches to stigma assessment, as inconsistencies in survey items and temporal mismatches between stigma and suicide data hinder efforts to draw conclusive inferences. By employing robust measurement tools and systematic surveillance of mental health attitudes on a multinational scale, future research can better illuminate the complex interplay between stigma and suicidal behavior, ultimately enhancing our efforts toward suicide prevention.